Waktu Optimum Hidrolisis Pati Limbah Hasil Olahan Ubi Kayu (Manihot esculenta Crantz var. Lahumbu) Menjadi Gula Cair Menggunakan Enzim Î±-Amilase Dan Glukoamilase - Ardiansyah, Ardiansyah; Nurlansi, Nurlansi; Musta, Rustam (Indonesian Journal of Chemical Research, 2018)
This study aims to determine optimum time of action of the enzyme Î±-amylase and glucoamylase needed in hydrolyze of starch from waste processed cassava (Manihot esculenta Crantz var. Lahumbu). This research was conducted through three main stages, namely the gelatinization, liquefaction and saccharification. The method was used method are liquefaction and saccharification. The variation time of the stage liquefaction: 12; 24; 36; 48; 60; and 72 minutes and the saccharification stage are: 9; 18; 27; 36; 45; 54; and 63 hours. The results showed that the optimum time required for stage liquefaction using Î±-amylase enzyme is 48 minutes on the condition of a temperature of 80 oC with a value of 0.09% amylose levels were measured using UV-Vis spectrophotometer. The optimum time required for saccharification step using a glucoamylase which is 54 hours on the conditions of a temperature of 50oC with the amount of reducing sugar concentration of 9.186 g/L as measured using a UV-Vis spectrophotometer.